Synthesis of 4H‑Pyrazolo[3,4‑d]pyrimidin-4-one Hydrazine Derivatives as a Potential Inhibitor for the Self-Assembly of TMV Particles - Wang, Ya; Guo, Shengxin; Sun, Wei; Tu, Hong; Tang, Yao; Xu, Ying; Guo, Renjiang; Zhao, Zhichao; Yang, Zhaokai; Wu, Jian (Journal of agricultural and food chemistry, 2024)
Tobacco mosaic virus coat protein (TMV-CP), as a potential target for the development of antiviral agents, can assist in the long-distance movement of viruses and plays an extremely important role in virus replication and propagation. This work focuses on the synthesis and the action mechanism of novel 4H-pyrazolo[3,4-d] pyrimidin-4-one hydrazine derivatives. The synthesized compounds exhibited promising antiviral activity on TMV. Specifically, compound G2 exhibited high inactivating activity (93%) toward TMV, slightly better than commercial reagent NNM (90%). The action of mechanism was further explored by employed molecular docking, molecular dynamics simulation, microscale thermophoresis, qRT-PCR, and transmission electron microscopy. Results indicated that G2 had the capability to interact with amino acid residues such as Trp352, Tyr139, and Asn73 in the active pocket of TMV-CP, creating strong hydrophobic interactions and thus obstructing the virus’s self-assembly.